UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA MELALUI PERAN KKN TEMATIK POSDAYA BERBASIS MASJID DUSUN MANGUNREJO DESA BLAMBANGAN - Riza Faishol; Ahmad Aziz Fanani (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2019)
The mosque is a center of religious activities and community empowerment. The majority of Blambangan Village People are employees in private factories,fishermen, and farmers. Judging by the average environmental Fakor is a hardworking citizen, we are carrying the theme